2001
DOI: 10.2165/00023210-200115080-00003
|View full text |Cite
|
Sign up to set email alerts
|

CNS Involvement in Primary Sj??gren??s Syndrome

Abstract: Among the systemic manifestations of primary Sjögren's syndrome, neurological involvement is still an intriguing and debated issue. Although peripheral nervous system abnormalities are a well documented occurrence with a reported prevalence ranging from 10 to 20%, opinions differ as to the prevalence of CNS disease, with suggestions from 'nonexistent' to 'very common'. The lack of agreement probably reflects the different populations selected, different inclusion criteria and lack of rigorous epidemiological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Women with pSS rated themselves higher on symptoms of somatization, depression, anxiety, and paranoid ideation than healthy controls (8). Other studies have reported cognitive impairment (9), psychosis (9, 10), mood disorders (1113), anxiety disorders (12, 13), somatization disorders (12), and dissociative states (12) or a combination of these in pSS patients. Despite this, very few published studies comprehensively phenotype the neuropsychiatric manifestations of pSS, disease course, and response to treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Women with pSS rated themselves higher on symptoms of somatization, depression, anxiety, and paranoid ideation than healthy controls (8). Other studies have reported cognitive impairment (9), psychosis (9, 10), mood disorders (1113), anxiety disorders (12, 13), somatization disorders (12), and dissociative states (12) or a combination of these in pSS patients. Despite this, very few published studies comprehensively phenotype the neuropsychiatric manifestations of pSS, disease course, and response to treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Anti-Ro/SSA and anti-La/SSB antibodies are positive in only 50% of patients. 3 Thus, the neurologic symptoms of SS are present in the absence of oral/ocular dryness. In such cases, the clinicians should have a high index of suspicion for pSS and consider autoantibody testing.…”
Section: Discussionmentioning
confidence: 99%
“…Among the neurological presentations, the involvement of the peripheral nervous system is seen more commonly with a frequency of around 10 to 20%. 2 3 The central nervous system (CNS) involvement is not well established, with a rate varying from 1.5 to 25%. 4 5 The CNS manifestations can be in a diverse spectrum and may manifest at onset or later during the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Movement disorders have been rarely described in association with pSS, and are less classic that in systemic lupus erythematous. There are few reports of chorea, dystonia, athetosis and tremor [ 20 ]. Extrapyramidal syndrome has been more frequently reported [ 21 24 ].…”
Section: Discussionmentioning
confidence: 99%